The role of effort expectancy and facilitating conditions in enhancing digital banking adoption: A pathway towards sustainable financial services - Zea, Diva Akiela Fahlerie; Halim, Rizal Edy (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: The adoption of digital banking has become increasingly important as financial institutions strive to enhance customer experience and service accessibility. However, the factors influencing users' intention to adopt digital banking remain complex. This study aims to explore the factors influencing the behavioral intention to adopt digital banking, focusing on these three key constructs. Methods: The study employs a quantitative research design using a survey to collect data from users of digital banking services. A structured questionnaire was developed to measure the three factors: performance expectancy, effort expectancy, and facilitating conditions. The data were analyzed using multiple regression analysis to assess the impact of each factor on users' intention to adopt digital banking. Findings: The results reveal that effort expectancy has the most significant positive influence on users’ intention to adopt digital banking. This suggests that the perceived ease of use plays a critical role in adoption decisions. Facilitating conditions, such as infrastructure and technical support, were also found to be important in encouraging users to engage with digital banking services. However, performance expectancy was found to have a statistically insignificant relationship with behavioral intention, which contrasts with prior studies that emphasize its importance. Conclusion: This study highlights the importance for banks to prioritize user-friendly platform design, minimize effort and complexity, while ensuring the availability of technical infrastructure and supporting systems. This study suggests that focusing on ease of use and providing enabling conditions are critical to increasing digital banking adoption rates and sustaining long-term user engagement. Novelty/Originality in this article: This article contributes to the existing literature by providing new insights into the role of effort expectancy in digital banking adoption, contrasting with prior research that emphasizes performance expectancy. It also highlights the significant role of facilitating conditions, offering practical recommendations for banks to enhance digital banking adoption by focusing on user accessibility and support systems.